Determinants of Stunting among Children Aged 12-60 months in South Central Timor Regency of Indonesia: A Cross-Sectional Study - Herliana Monika Azi Djogo; Yasinta Betan; Yohanes Dion (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: Stunting is currently one of the world's nutritional problems suffered by toddlers. This study aimed to determine the factors and incidence of stunting among children aged 12-60 months old in Indonesia. Methods: The design was a cross-sectional approach. This research was conducted in the South Central Timor Regency from February to August 2020. The respondents of this study were as many as 286 mothers and children. The sampling technique used in this study was purposive sampling. The questionnaire was used to identify demographic factors, infectious diseases, maternal care practice factors and stunting was identified by using the anthropometric measurement by WHO age-based height index (Z score <-2 SD). Chi-square and logistic regression were used to determine the factors associated with the incidence and the dominant factors of stunting. Results: The results showed a significant relationship between the number of children with p= 0.000; mother's knowledge with p= 0.000; and practice of complementary feeding with the incidence of stunting with p=0.000, while the main factor causing the incidence of stunting in toddlers is the number of children, which is more than two people in the family (p= 0.000, Exp (B) = 0.137). Conclusion: The number of children is the primary factor causing stunting in South Central Timor. Therefore, health workers should increase health promotion and education about stunting and raise family awareness in running family planning programs to meet children's needs, including nutrition and control of childbirth.